Recurso educativo y aprendizaje del manejo de sondas dirigido a estudiantes de medicina de la Universidad Nacional de Loja - Herrera Diaz, Michelle Katherine (2024)
Clinical simulation has allowed students to improve their skills for a practical experience very close to reality, recreating clinical scenarios and facing situations that can be found in the professional field, being possible immediate feedback for continuous improvement learning. For this reason, the general objective of this research work was: To create educational resources for the learning of probe management based on simulation for students of Carrera de Medicina at Universidad Nacional de Loja; and the specific objectives were: To develop a practical guide for the practice of simulation-based probe management for students of Carrera de Medicina at Universidad Nacional de Loja: To develop a practice guide for the learning of probe management for medical students; to make a video as an educational resource to reinforce the learning of simulation-based probe management for medical students; to evaluate the learning acquired based on the educational resource through Examen Clínico Objetivo Estructurado (ECOE) applied to medical students.This is a mixed prospective cross-sectional cohort study in which 38 students of the tenth cycle of Carrera de Medicina Humana participated, to whom the workshop with the developed educational resources was given, subsequently knowledge was evaluated by applying the ECOE; obtaining that 57.89% (n=22) of the participants obtained an outstanding qualification when performing 17 activities of the ECOE, while 42. 11% (n=16) achieved a rating of very good by performing 15 to 16 activities of the ECOE correctly with an approval of the total number of participants, this shows that the educational resources implemented contributed significantly to the development of skills for learning how to handle probes. It is concluded that the educational resources encourage more active, participatory learning and effective communication skills, which are important for medical practice